1998
DOI: 10.1111/j.1745-6592.1998.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Vertical Circulation Column: Containment System for Small‐Scale DNAPL Field Experiments

Abstract: The in situ vertical circulation column (ISVCC) is a cylindrical containment system consisting of an instrumented steel cylinder used for experimental ground water studies in sandy aquifers. Vertical flow is imposed inside the ISVCC. Although vertical wells are an option, the ISVCC installed in the Borden Aquifer is instrumented with horizontal wells and monitoring ports to avoid creating vertical preferential flow paths. The cylinder was driven downward into the aquifer using a small backhoe equipped with a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Remediation technologies based on reductive dechlorination by vitamin B 12 have been developed and have potential for treating chlorinated organic contaminants in groundwater. [1][2][3][4] It is important to investigate the reaction pathways involved in remedial technologies. Effective remediation also requires detailed knowledge of the extent to which the contaminants at a site are degraded.…”
Section: Introductionmentioning
confidence: 99%
“…Remediation technologies based on reductive dechlorination by vitamin B 12 have been developed and have potential for treating chlorinated organic contaminants in groundwater. [1][2][3][4] It is important to investigate the reaction pathways involved in remedial technologies. Effective remediation also requires detailed knowledge of the extent to which the contaminants at a site are degraded.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B12 (cyanocobalamin) has been used, as a substitute for anaerobic bacteria, in biomimetic systems to conduct studies on the mechanism of reductive dechlorination ( ). It has also been used as a groundwater remediation method ( ). Reductive dechlorination occurs naturally at some, but not all, contaminated sites requiring remedial action.…”
Section: Introductionmentioning
confidence: 99%
“…Nash commented that the extremely high concentrations of oil and grease which were present may have caused the observed clogging of the field test holes and thus restricted flow of the surfactant solution through the contaminated regions. Field testing showed ineffective removal of contaminants where low hydraulic conductivity beds are present in the aquifer (Sorel et a!., 1998). Ang and Abdul (1991) reported that about 80% of polychlorinated biphenyls (PCBs) can be washed from sandy soils in laboratory and field experiments.…”
Section: Summary Of Related Research In Surfactant-assisted Remediationmentioning
confidence: 99%